Length of the Mitral Isthmus But Not Anatomical Location of Ablation Line Predicts Bidirectional Mitral Isthmus Block in Patients Undergoing Catheter Ablation of Persistent Atrial Fibrillation: A Randomized Controlled Trial. (29th April 2015) - SCHERR, DANIEL; DERVAL, NICOLAS; SOHAL, MANAV; PASCALE, PATRIZIO; WRIGHT, MATTHEW; JADIDI, AMIR; KOMATSU, YUKI; ROTEN, LAURENT; WILTON, STEPHEN B.; PEDERSEN, MICHALA; RAMOUL, KHALED; MIYAZAKI, SHINSUKE; et al.
Importance of Line and Length for Mitral Isthmus Introduction Mitral isthmus (MI) ablation is an effective option in patients undergoing ablation for persistent atrial fibrillation (AF). Achieving bidirectional conduction block across the MI is challenging, and predictors of MI ablation success remain incompletely understood. We sought to determine the impact of anatomical location of the ablation line on the efficacy of MI ablation. Methods and Results A total of 40 consecutive patients (87% male; 54 ± 10 years) undergoing stepwise AF ablation were included. MI ablation was performed in sinus rhythm. MI ablation was performed from the left inferior PV to either the posterior (group 1) or the anterolateral (group 2) mitral annulus depending on randomization. The length of the MI line (measured with the 3D mapping system) and the amplitude of the EGMs at 3 positions on the MI were measured in each patient. MI block was achieved in 14/19 (74%) patients in group 1 and 15/21 (71%) patients in group 2 (P = NS). Total MI radiofrequency time (18 ± 7 min vs. 17 ± 8 min; P = NS) was similar between groups. Patients with incomplete MI block had a longer MI length (34 ± 6 mm vs. 24 ± 5 mm; P < 0.001), a higher bipolar voltage along the MI (1.75 ± 0.74 mV vs. 1.05 ± 0.69 mV; P < 0.01), and a longer history of continuous AF (19 ± 17 months vs. 10 ± 10 months; P < 0.05). In multivariate analysis, decreased length of the MI was an independent predictor of successful MI block (OR 1.5; 95% CI 1.1–2.1; P < 0.05). Conclusions Increased length but not anatomical location of the MI predicts failure to achieve bidirectional MI block during ablation of persistent AF.